(untitled) (Bangladesh Journal of Medical Science, 2023)
Introduction: Neonates undergo major physiologic changes during transition from intrauterine to extra-uterine period. Although, this transition is smooth mostly, 5-10% needs some assistance in breathing. The indications and timing of supplemental oxygen therapy to assist the newborn in this transition has been a matter of debate. Objective: To observe the range of oxygen saturation among healthy newborns in the first 10 minutes of life and to compare those with different gestation and mode of delivery. Materials and Methods: This cross-sectional study was conducted in the Department of Obs & Gynae, BSMMU for 9 months. All healthy neonates born by normal vaginal or cesarean delivery were included. For each newborn, oxygen saturation was recorded at 1, 5, and 10 minutes after birth and every 5 minutes thereafter till readings from both these sites crossed 90% and equalized. Parents were interviewed with a specific pre-designed and pre-tested questionnaire. Collected data were analyzed by using SPSS v20. Results: A total of 300 newborn data were analyzed. Newborns who were born by cesarean delivery had lower SpO2 than infants born vaginally (p <0.001) and they took longer time to reach SpO2>85%. The median SpO2 did not reach 90% until 5 minutes of life in either group. Significant difference in oxygen saturation was also found at 1, 5 & 10 minutes of life between pre-term & and term newborns (P value <0.001). Conclusion: Oxygen saturation was low in babies who were delivered by cesarean section compared to those delivered by normal vaginal route. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 368-373